Enhancement mechanisms of water vapor adsorption rate onto silica-gel in acoustic field. (February 2020) - Fujiki, Junpei; Nakayama, Masayuki; Ueda, Yuki; Akisawa, Atsushi
Highlights: Water vapor adsorption kinetics with and without acoustic field was evaluated. Fluid film mass transfer was enhanced via velocity amplitude of the acoustic field. The enhanced adsorption kinetics would be involved with the thinning of fluid film. The diminished mass transfer was observed in some cases. Oscillation flow to steady flow ratio was a significant factor for the enhancement. Abstract: This study was focused on the evaluation of the adsorption kinetics of water vapor onto silica-gel with and without an acoustic field, in an objective to reveal the enhancement mechanisms of water vapor adsorption by an acoustic wave. Adsorption uptake curves of water vapor from humidified air onto the silica-gel with and without acoustic field were measured at room temperature under various conditions, after which the adsorption kinetic parameters (fluid film mass transfer coefficient and intraparticle diffusivity) were determined from the uptake curves with the aid of numerical calculations. The results demonstrated that the acoustic field exhibited no effect on the intraparticle diffusion, because the fluid film mass transfer was the rate-limiting step under the condition of this study. In contrast, the fluid film mass transfer was enhanced by the velocity amplitude of the acoustic field. However, the diminished mass transfer was also observed in some cases. For the enhancement and diminution of adsorption rate by the acoustic wave, it was suggested that the ratio of the oscillation flow ( U ) to the steady flow ( u ), U ' =  U / u, was an important factor. Moreover, the enhanced adsorption kinetics was observed under the conditions of U ' > 2, whereas the adsorption rate was diminished or invariant under the condition of U ' < 2. This would be understood from the viewpoint of the thinning and thickening of fluid film by the oscillation flow caused by the acoustic wave. Even when the direction of the oscillation flow is countercurrent to the steady flow, the thinning of fluid film by the oscillation flow is still possible under U ' =  U / u  > 2.